KESESUAIAN ISI TALK SHOW MATA NAJWA DI METRO TV DENGAN SYARATSYARAT KARYA JURNALISTIK - Achmad Budiman Sudarsono (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
Today more prevalent events in the television talk show with the theme and nature that is differentevents. Talk Show is a blend of art and engineering stage journalistic interview. Talk Show it seems tostill be one of the events most in demand by audiences in Indonesia and for the segments and themestaken can also vary. Mata Najwa event at Metro TV including one flagship talk show program. Talkshow is one of the works of journalism that discusses the hot issues in which a work of journalismmust fulfill the terms of journalistic work. This study aims to determine the extent of compliance to thecontent of the talk show Mata Najwa with the terms of the journalistic work of the period 18 Februaryto 29 April 2015. The paradigm used in this research is the paradigm of positivism, the approach usedis quantified by the method of content analysis and research which is a descriptive study thatillustrates just do not generalize. Results of this study stated that of the 10 samples of the news, in thecategory of terms work jurnalistikterdapat 7 news (70%) that meets the requirements of journalisticwork well, 3 samples (30%) did not meet the requirements of journalistic work well, especially inWarm problem categories, the actual, unbiased and balanced. 1 among the 3 samples that do not meetthe requirements of journalistic work well is the news that did not meet the category of trust of viewersbecause it is considered that given the lack of in-depth information and siding.Keywords: Talk Show, Media Television, and Journalism